The Role of Income Distribution through ZIS in Realising Economic Justice in Indonesia - Adriani, Siti Kamiliyah; Arifin , Sirajul (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study investigates the persistent structural gap between the theoretical potential and realized implementation of Zakat, Infaq, and Sadaqah (ZIS) as Islamic fiscal instruments for equitable income redistribution in Indonesia. Drawing on consolidated national data from the National Zakat Agency (BAZNAS), Indonesia's annual zakat potential is estimated at IDR 327.6 trillion. However, actual ZIS collections consistently fall short: IDR 12.7 trillion in 2020, IDR 14.7 trillion in 2021, IDR 22.2 trillion in 2022, and IDR 28.7 trillion (provisional) in 2023 .  The 2023 realization represents merely 8.8% of total potential, leaving over IDR 298.9 trillion unutilized and signalling systemic inefficiencies in philanthropy governance. Employing a library research methodology that analyzes BAZNAS datasets, BPS poverty metrics, and Islamic economics literature, this study identifies three primary constraints: fragmented institutional coordination between ZIS management and fiscal authorities; deficiencies in public financial literacy regarding contemporary zakat obligations; and inadequate digital infrastructure for transparent distribution.Modelling based on BAZNAS-BPS data indicates that harnessing just 30% of ZIS potential (approximately IDR 98.3 trillion) could significantly reduce Indonesia's Gini coefficient by 0.03 points and alleviate extreme poverty for 4.2 million citizens. This paper concludes by advocating for integrated policy reforms centered on digitalized collection systems, sharia-compliant fiscal integration, and targeted religious education to transform ZIS into an effective redistributive mechanism aligned with the maq??id al-shar??a (higher objectives of Islamic law).